Distinctive features of obligation fulfillment in civil relations complicated by smart contracts - Isakulova Elmira (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
the integration of smart contracts into civil law relations introduces a paradigm shift in how obligations are formed, executed, and enforced. This article examines the distinctive legal and practical aspects of fulfilling obligations in civil transactions involving smart contracts, with a particular focus on challenges within the legal framework of Uzbekistan. Drawing on international experience and scholarly sources, the study highlights the gap between the technological logic of smart contracts and the foundational principles of traditional civil law